On the Multiscale Computation of Defect Driving Forces - Mergheim, Julia; Steinmann, Paul; Ricker, Sarah (International Journal For Multiscale Computational Engineering, 2009)
In the present contribution, the computational homogenization scheme is extended toward the homogenization of configurational quantities like the Eshelby stress and material node point forces. Configurational mechanics is concerned with changes of the material configuration of continuum bodies and has numerous applications in defect mechanics, as, e. g., it can be shown that the material force at a crack tip corresponds to the J-integral and thus yields a criterion for crack propagation. In the theoretical part of this work, the differences between the homogenization of the direct and the inverse motion problem are elaborated. Therefore focus is put onto the influence of microscopic material interfaces and material body forces on the averaged field values. The theoretical results are illustrated by various numerical examples, which on one hand compare the homogenized configurational quantities for different microstructures, and on the other hand, point out which features of the microstructure influence the macroscopic configurational quantities. © 2009 by Begell House, Inc.
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-TM.onthem_2
Keywords: Configurational forces; Homogenization; Multi-scale